2018
DOI: 10.24875/ric.18002527
|View full text |Cite
|
Sign up to set email alerts
|

Use of Functional Foods and Oral Supplements as Adjuvants in Cancer Treatment

Abstract: In cancer patients treated with radiotherapy to the abdominopelvic region, dietary modifications and the use of functional foods (fortified food with added ingredients to provide specific health improving benefits, such as antioxidants, omega-3 fatty acids, and glutamine), may contribute to the improvement of the toxic effects of treatment, including nausea, diarrhea, and constipation, among others. With the aim of analyzing which coadjuvant foods benefit these patients, scientific evidence was gathered by a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 31 publications
2
19
0
10
Order By: Relevance
“…Interestingly, diarrhea was also significantly reduced in the ONS group (Table II). Several reports have shown that glutamine can contribute to improving the toxic effects of chemotherapy, such as diarrhea, constipation, and nausea (24,25), and therefore it seems reasonable that HMB, L-arginine and L-glutamine supplementation can also be preventive against sorafenibinduced diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, diarrhea was also significantly reduced in the ONS group (Table II). Several reports have shown that glutamine can contribute to improving the toxic effects of chemotherapy, such as diarrhea, constipation, and nausea (24,25), and therefore it seems reasonable that HMB, L-arginine and L-glutamine supplementation can also be preventive against sorafenibinduced diarrhea.…”
Section: Discussionmentioning
confidence: 99%
“…These products known as probiotic supplements have been extensively studied over recent years, indicative benefits have been reported such as their ability to neutralise toxins (Corbo et al ., ); good sensory characteristics when microencapsulated (Mokhtari et al ., ) and superior survival and transition through the gut (Campaniello et al ., ). They have also been developed with a range of fortification approaches to further improve health benefits, such as the addition of linoleic acid (Abd El‐Salam et al ., ); green tea fortified with soy (Moumita et al ., ); supplemented with Vitamin D as an aid to weight loss (Mohammadi‐Sartang et al ., ); added to fruit juices (Ephrem et al ., ) and as an adjuvant or a prophylactic therapy in cancer treatment (Serna‐Thome et al ., ; Wardill et al ., ).…”
Section: Probioticsmentioning
confidence: 98%
“…Glutamic acid is a nonessential amino acid and has functions that allow it to interact with other biological biomolecules in order to maintain energy between tissues for the synthesis of molecules and lead to cell growth [1].…”
Section: Glutamic Acidmentioning
confidence: 99%
“…This compound also participates in the metabolism of carbohydrates and in the cellular respiration process of the Krebs cycle [1].…”
Section: Glutamic Acidmentioning
confidence: 99%
See 1 more Smart Citation